STUDYING ADVANCED EXPERIENCES IN THE PREVENTION OF THEFT CRIMES IN FOREIGN COUNTRIES - Khasanov Shukhrat Erkinbayevich (PT. Antis International Publisher, 2026)
Objective: This study aims to analyze the effectiveness of theft crime prevention strategies in Uzbekistan, focusing on adapting international best practices to local legal, social, and cultural contexts. Method: Utilizing comparative criminological methods, the study incorporates doctrinal analysis and policy comparison, examining prevention models from the United States, United Kingdom, Germany, Japan, Singapore, and select European countries. Results: The analysis reveals that theft prevention is most effective when integrating modern technologies such as video surveillance, biometric identification, digital monitoring systems, and data-driven policing with social measures like community engagement, neighborhood watch programs, environmental design, and preventive education. The study shows that countries with strong policies on early intervention, public involvement, and technology experience fewer robbery-related offenses. Novelty: This research highlights the failure of direct transplantation of international models without adaptation to local realities and proposes a contextually framed application of advanced preventive practices, supported by legal education and community-based initiatives. The findings provide a solid foundation for policymakers and law enforcement to implement modern, sustainable, and society-oriented crime prevention strategies.